Here’s another for you people – 5/6k = 1/6

Question

Here’s another for you people – 5/6k = 1/6

0

Answers ( No )

    0
    2021-09-06T09:06:23+00:00

    Solve for k:
    (-5 k)/6 = 1/6

    Multiply both sides of (-5 k)/6 = 1/6 by -6/5:
    (-6 (-5) k)/(5×6) = ((-6)/5)/6

    (-6)/5×(-5)/6 = (-6 (-5))/(5×6):
    (-6 (-5))/(5×6) k = ((-6)/5)/6

    ((-6)/5)/6 = (-6)/(5×6):
    (-6 (-5) k)/(5×6) = (-6)/(5×6)

    (-6)/6 = (6 (-1))/6 = -1:
    (-5-1 k)/5 = (-6)/(5×6)

    (-5)/5 = (5 (-1))/5 = -1:
    –1 k = (-6)/(5×6)

    (-1)^2 = 1:
    k = (-6)/(5×6)

    (-6)/6 = (6 (-1))/6 = -1:
    Answer: k = (-1)/5

Leave an answer

Browse
Browse